Pharmacokinetics and thermal anti-nociceptive effects of oral morphine in horses - Heather K. Knych; Heather K. Knych; Stacy J. Steinmetz; Megan L. Traynham; Daniel S. McKemie; Philip H. Kass (Frontiers in Veterinary Science, 2024)
IntroductionMorphine is an effective analgesic in horses, however, IV administration at therapeutic doses has been shown to produce dose-dependent neuroexcitation and unwanted gastrointestinal effects. The analgesic effects of morphine have, at least in part, been attributed to the morphine-6-glucuronide (M6G) metabolite. Oral administration to horses results in comparable M6G concentrations to that achieved following IV administration of a therapeutic dose without the adverse effects. The anti-nociceptive effects have not yet been reported. In the current study the thermal anti-nociceptive effects of single and multiple oral doses of morphine were assessed.MethodsSix horses received a single 0.2 mg/kg IV dose of morphine and multiple oral doses of 0.8 mg/kg morphine every 12 h for 4.5 days. Blood samples were collected throughout administration, morphine, and metabolite concentrations determined and pharmacokinetic analysis performed. Drug related behavior and physiologic responses were recorded. Response to noxious stimuli was evaluated by determining thermal threshold latency in response to the application of heat.ResultsThe maximum concentrations of M6G were higher following oral administration compared to IV and the combined morphine and M6G concentrations exceeded that of IV administration starting at 2 h. Oral administration of 0.8 mg/kg morphine provided and maintained comparable anti-nociception effects to IV morphine with less adverse effects, following single and multiple doses. Morphine was well tolerated following oral administration with less excitation and minimal effects on gastrointestinal borborygmi scores compared to IV administration.DiscussionResults of the current study warrant further investigation of the anti-nociceptive effects of oral morphine administration to horses.